Chemical compositions and characteristics of farm raised giant catfish (Pangasianodon gigas) muscle - Chaijan,M. (Academic Press Inc., 2015)
Proximate composition, chemical and physical properties of dorsal, ventral and lateral line cuts of farm raised giant catfish were determined. Protein, fat and ash content of the different cuts averaged 16.88, 4.45 and 1.24 g/100 g, respectively. Dorsal contains higher protein concentrations (19 g/100 g) than other two parts (p < 0.05). Ventral showed the highest hydroxyproline content (0.83 mg/g). Differences in lipid composition and fatty acid profiles were found among different cuts with highest phospholipids in the dorsal and highest triglyceride in both ventral and lateral line (p < 0.05). All the meat cuts contained high saturated fatty acid, followed by mono- and polyunsaturated fatty acid. High muscle hardness and toughness was found in the dorsal than that in the ventral (p > 0.05). The highest content of myoglobin and total pigment in lateral line resulted in the highest redness index (a*/b*) of this part. Three major nitrogenous compositions classified based on solubility in giant catfish muscle were myofibrillar, sarcoplasmic and alkaline soluble proteins. © 2009 Elsevier Ltd. All rights reserved.